2010
DOI: 10.1161/circulationaha.110.937136
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Nonsustained Ventricular Tachycardia After Non–ST-Elevation Acute Coronary Syndrome and Sudden Cardiac Death

Abstract: Background-Most studies examining the relationship between ventricular tachycardia (VT) after acute coronary syndrome and sudden cardiac death (SCD) were performed before widespread use of reperfusion, revascularization, or contemporary medical therapy and were limited to ST-elevation myocardial infarction. The incidence and prognostic implications of VT in patients with non-ST-elevation acute coronary syndrome receiving contemporary care have not been examined. Methods and Results-The Metabolic Efficiency Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(32 citation statements)
references
References 38 publications
1
27
0
4
Order By: Relevance
“…No randomized trials Observational study: nonpredictive of arrhythmic death 48 No randomized trials Observational studies: predictive 57,58 and nonpredictive 59 of arrhythmic death Nonsustained VT Randomized ICD trials: no survival benefit (combined with LVEF) 17 Observational study: predictive of arrhythmic death 60 Randomized ICD trials: survival benefit (combined with LVEF and a positive EPS) 15 …”
Section: Qrs Durationmentioning
confidence: 99%
“…No randomized trials Observational study: nonpredictive of arrhythmic death 48 No randomized trials Observational studies: predictive 57,58 and nonpredictive 59 of arrhythmic death Nonsustained VT Randomized ICD trials: no survival benefit (combined with LVEF) 17 Observational study: predictive of arrhythmic death 60 Randomized ICD trials: survival benefit (combined with LVEF and a positive EPS) 15 …”
Section: Qrs Durationmentioning
confidence: 99%
“…According to MERLIN‐TIMI 36 trial,10 ranolazine suppresses ventricular arrhythmias during the first week after admission for non‐ST elevation acute coronary syndrome, which can decrease the incidence of sudden cardiac death 22. Additionally, the RAID trial showed that ranolazine can significantly decrease VT episodes requiring antitachycardia pacing (ATP) compared to placebo patients while did not show a significant difference in the combined endpoint VT/VF or death.…”
Section: Resultsmentioning
confidence: 99%
“…According to MERLIN‐TIMI 36 trial, ranolazine suppresses VA during the first week after admission for non‐ST elevation acute coronary syndrome 14. In such patients, even short VT episodes of only few beats are associated with the risk of sudden cardiac death 19.…”
Section: Discussionmentioning
confidence: 99%